The Effect of Non-Genetic Traits on Physical and Chemical Milk Characteristics of Awassi Ewes - Baker, Ahmed Gh.; Shaker, Ahmed S. (American Journal of Biodiversity, 2025)
An experiment was conducted in the Animal Production Department, College of Agriculture/ Kirkuk University to find out the effect of some lactation traits on the physical and chemical properties of milk from Awassi ewes. Experimental Group In all experimental groups, 15 healthy lactating ewes (2–3 yr) were selected based on maternal ewe age, offspring sex and type of partum. The animals were all housed under standard conditions (identical diet, as well as environmental and husbandry practice). Monthly hydraulic milk samples were obtained in from the both state and tested for the action of milk fat, protein, lactose, SNF (solids-not-fat), and freezing level of milk as properly as different of the physic properties of milk had been markedly determined as per the well-known methods. Data were statistically analysed in SPSS, with a level of significance of p ≤ 0.05. Abstract Ewe age had a significant effect on the various properties of milk. The proportion of fat in milk was greater in the second (298 g of fat/kg of milk) and lesser in the third (176 g of fat/kg of milk) lactation (2.96% versus 1.76% respectively). Indeed, the ages significantly affected SNF, protein, and density of milk. Such changes are thought to result from functional and aging alterations in mammary gland physiology. There were significant (P < 0.05) differences between offspring sex for fat with milk from ewes lambing females containing significantly (2.76%) more fat than those from ewes lambing twin females (0.94%). Maternal sex-biased investment appears in the output. Apart from the parity, the birth type also had an effect on the percentage of fat in the milk: milks from nulliparous, single-born lamb ewes and multiparous, twin-born lamb ewes were richer in fat (2.59%) than milks from ewes with twins (1.46%), because twins diluted the fat with higher milking output in these ewes than of the single-born ones. The parameters (Especially fat) in composition of milk from Awassi sheep are affected based on the age of Ewe, and the sex of Offspring and Lambing type. These findings draw attention to the importance of non-genetic dairy ewe management for milk quality and production output when subjected to varying environmental and physiological factors.